A enfermagem e o processo de educação permanente em saúde no contexto hospitalar - Santarem, Daniela (Universidade do Vale do Rio dos Sinos, 2016)
This master thesis presents the process of research and deployment of permanent education in health (PEH) by the nursing staff of Intensive Care Unit of a military Hospital in southern Brazil. Objectives: develop an institutional proposal for permanent health education with the nursing staff of the Intensive Care Unit of the Military Hospital in Canoes. Method: it was performed a qualitative, descriptive research in light of the assumptions of Permanent Health Education, and theoretical-methodological contributions of action research. Eight wheels of conversations were made with all workers in the ICU nursing. The information collection techniques were the "wheels of conversation", mediated by the research goals and their respective themes generators. Results: by means of thematic analysis of the nuclei of meaning produced, four subcategories were present, repeatedly throughout the process, but differing in order of prevalence or importance: assistance and their workflows, space/physical resources; materials and equipment; relationships/working conditions; and "training". In the analysis of its senses and how summary of first wheels and generators, whose reflection object turned around the critical nodes of the work itself, emerged the category the work alive in act: the production of care. The second category emerged from the analysis of the relationship of the four subcategories with the focus of the subsequent discussions in the last two wheels, which is: dialogue and looking for overcoming critical nodes projective identified. Its theoretical density resulted in name it as: EPS: a constitutive dimension of the work alive. Both interlaced, keep in common the insolvable association between attention, management, educative act at health work and the participative process initiate by the research. Final considerations: it was observed that the dialogic process provided by the wheels, the design of education at work as vertical and technological process was giving space to the emerging vision of permanent education in health, where purchasing centrality exchanges of experiences and knowledge among health workers and the user-centered care model. The implementation of a policy of permanent health education in the hospital represents a challenge of rupture and breaking paradigms. Recognizing the centrality of the work and the worker in a model of user-centered health requires incorporating the sense of collective, approaching the professionals, patients, the technical areas and lines of support care that articulate knowledge, managerial processes and assistance to contexts and working relationships.
Keywords: Educação permanente; Educação continuada; Enfermagem; Prática profissional; Hospital; Permanent education; Continuing education; Nursing; Professional practice; The health team; ACCNPQ::Ciências da Saúde::Enfermagem